The Effect of PjBL with WBL Media and Cognitive Style on Students’ Understanding and Science-Integrated Concept Application (Jurnal Pendidikan IPA Indonesia, 2020)
The purpose of this study is to find out the effect of PjBL with WBL media as an instructional strategy and direct instructional (DI) strategy on the understanding (intercept) and the concept application of science-integrated learning media. The method of this research is Quasi-Experimental with 2x2 factorial design. The number of respondents is 110 pre-service teachers consisting of 68 respondents for the experimental class and 42 respondents for the control class. The sampling technique is purposive sampling with a class as an experimental class and another class as a control class. MANOVA is used to analyze the data. The result of the test shows that: (1) there is a difference in the average score of learning outcomes in understanding and science-integrated conceptual application among pre-service teachers who are taught with Web-based PjBL and DI strategies. The average score of understanding the concept of developing science-integrated learning media with a Web-based PjBL strategy is 88.81, DI is 85.69. The average score of the concept application with Web-based PjBL strategy is 89.07, DI is 85.69; (2) there are differences in the average score of understanding learning outcomes and the application of the concept of developing science-integrated learning media between pre-service teachers who have a cognitive style of FD and FI. The average score of understanding the concept of FD is 88.08, FI is 86.12. The average score of the concept application FD is 87.37, FI is 88.29. From these data, it can be concluded that the Web-based PjBL strategy has a better contribution than DI in improving the learning outcomes of understanding and application of the concept of developing science-integrated learning media.